Obstructive-Type Jaundice without Bile Duct Dilatation in Generalized Peritonitis Is a Specific Sign of Spontaneous Gall Bladder Perforation - Vicky Sumarki Budipramana; Maria Meilita (Case Reports in Medicine)
Generalized peritonitis caused by spontaneous gall bladder perforation is rare and difficult to diagnose preoperatively. The increased absorption of the spilling conjugated bile from the gall bladder by the inflamed peritoneum causes jaundice and direct hyperbilirubinemia. A 56-year-old male patient with septic generalized peritonitis and obstructive-type hyperbilirubinemia came to our hospital. The blood examination showed that total, direct, and indirect bilirubin were 6.20, 5.38, and 0.82 mg/dl. The gall bladder perforation was not detected on USG, CT scan, and MRCP. On laparotomy, we found a 0.5 cm perforation on the fundus of the gall bladder and 2500 cc of bilious fluid in the peritoneal cavity. Cholecystectomy was performed, and the patient completely recovered after the surgery. Preoperative diagnosis of spontaneous gall bladder perforation is difficult even by using ultrasonography, CT scan, and MRCP. The inflammatory reaction of the peritoneum in bile peritonitis increases the absorption of the spilled conjugated bile from the peritoneal cavity. The obstructive-type hyperbilirubinemia without dilatation of the bile duct on imaging examination was the sign of bile leakage into the peritoneal cavity. In septic condition, the preoperative diagnosis of the spontaneous gall bladder perforation is important to establish so that the surgeon can make only a minimal procedure in reducing the morbidity. Therefore, it could be concluded that the presently occurring obstructive-type jaundice without dilatation of the bile duct in the case of generalized peritonitis is a specific sign of spontaneous gall bladder perforation.